IMPLEMENTATION OF THE PIERCING THE CORPORATE VEIL PRINCIPLE IN THE LIMITED LIABILITY COMPANY LAW - Angga Zalayeta; Maroni; Maya Shafira; Gunawan Jatmiko; Deni Achmad (Sriwijaya Crimen and Legal Studies, 2025)
Efforts to protect stakeholder interests in a Limited Liability Company, especially related to the opportunity for shareholders to take legal action, including influencing the company in such a way that it is contrary to the principles of propriety and justice and to provide legal support for the existence of the company's board of directors and board of commissioners in carrying out their respective duties, then a legal doctrine has developed in corporate law which is often called Piercing the Corporate Veil. Judging from the substance of the material and idealism contained in this corporate law doctrine, the intended doctrine is actually needed as part of controlling the morals of the individuals standing behind the company's organs in running their business so as not to commit reprehensible acts that can harm the sense of justice of the community. Therefore, these corporate law doctrines are very important. Business entities in the business world are known as both those that are already in the form of companies and those that are not yet in the form of companies. Based on their legal form, companies are divided into two, namely companies that have legal entity status and those that are not legal entities. As an independent legal entity, the liability of PT shareholders is only limited to the value of the shares owned in the company. The doctrine of piercing the corporate veil can be applied in a Limited Liability Company in the event of misleading facts, fraud and injustice and to protect minority shareholders, shareholders concerned either directly or indirectly in good faith who use the company solely for personal interests.